Comparative Efficacy of Apixaban, Dabigatran, Clopidogrel, and Aspirin Against Ferric-Chloride-Induced Thrombosis in the Carotid Arteries of Rats - Arif, Hawkar H.; Maulood, Ismail M. (Kurdistan Journal of Applied Research, 2026)
Carotid injury induced by ferric chloride (FeCl₃) is a model of arterial thrombosis for evaluating antithrombotic medications. Preclinical comparisons of different drug classes are scarce. This study compared the efficacy and safety of two direct oral anticoagulants (DOACs)—apixaban and dabigatran—and two antiplatelet agents—clopidogrel and aspirin. Adult male rats were randomly assigned to control, FeCl₃, and FeCl₃ with apixaban, dabigatran, clopidogrel, and aspirin. The endpoints were thrombus weight, occlusion time (OT), bleeding time (BT), capillary-tube clotting time (CT), and blood count. In addition, serum thromboxane B2 (TXB₂), D-dimer, malondialdehyde (MDA) and histopathological examination of the carotid artery were investigated. Compared to the controls, FeCl₃ caused a rapid, platelet-rich occlusion with increases in thrombus weight (7.18 mg), D-dimer (708.7 ng/mL), TXB₂ (549.7 pg/mL), and MDA (6.76 µmol/L). All treatments significantly prolonged OT compared with the FeCl₃ group. The DOACs (dabigatran and apixaban) demonstrated superior overall efficacy, prolonging OT and CT, reducing thrombus weight (2.53–3.97 mg) and D-dimer (563.8–591.8 ng/mL), and preserving arterial architecture, but with significant BT prolongation. Clopidogrel reduced thrombus weight (4.18 mg), TXB₂, D-dimer (552.2 ng/mL), and MDA (4.19 µmol/L) without affecting CT and with intermediate effects on BT. Aspirin showed relatively modest effects across all outcomes. Anticoagulants also reduced histological damage and normalised leukocyte counts. The efficacy of the anticoagulants reflected their mechanistic targets in FeCl₃-induced carotid thrombosis, following the gradient of dabigatran ≈ apixaban > clopidogrel >> aspirin. In this platelet-dominant model, clopidogrel was surprisingly effective, whereas aspirin had effects. DOACs offered the inhibition of thrombus formation, albeit at the expense of increased bleeding liability.